2020
DOI: 10.1080/17441692.2020.1812103
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic and Rohingya refugees in Bangladesh: What are the major concerns?

Abstract: The COVID-19 pandemic is now a global crisis and the Rohingya refugees in Bangladesh are in the most vulnerable situation. Lack of access to services that are considered critical and life-saving such as food, drinkable water, and shelter, together with limited access to health services are turning an already serious crisis into a major human disaster. Meanwhile, there are concerns that Rohingya refugees are already in too poor health to ward off the COVID-19. Access to the abovementioned facilities and trustwo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 4 publications
0
28
0
Order By: Relevance
“…Pre-COVID-19, Rohingya refugees were already suffering from insufficient essential services such as food, education, water and sanitation, and basic health care ( Banik et al., 2020 ; Islam and Nuzhath, 2018 ). For adolescents, the focus of this paper, previous mixed-methods research in Cox's Bazar found that Rohingya adolescent girls and boys are a particularly marginalised subpopulation that is failing to develop their full cognitive, emotional and social capabilities due to their precarious displacement status ( Gender and Adolescence: Global Evidence (GAGE) 2020 ; Guglielmi et al., 2020 a; 2020 b; 2020 c; 2020 d; Bakali and Wasty, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pre-COVID-19, Rohingya refugees were already suffering from insufficient essential services such as food, education, water and sanitation, and basic health care ( Banik et al., 2020 ; Islam and Nuzhath, 2018 ). For adolescents, the focus of this paper, previous mixed-methods research in Cox's Bazar found that Rohingya adolescent girls and boys are a particularly marginalised subpopulation that is failing to develop their full cognitive, emotional and social capabilities due to their precarious displacement status ( Gender and Adolescence: Global Evidence (GAGE) 2020 ; Guglielmi et al., 2020 a; 2020 b; 2020 c; 2020 d; Bakali and Wasty, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…In an attempt to define tourist knowledge, Tsaur et al (2010) showed that travel-related information and skills represent tourists' perception of associated knowledge about any travel. In this case, declarative knowledge refers to tourist's perception of the specific travel destination and procedural knowledge denotes the practical use the knowledge by tourists in the traveling period starting from planning to the end of the trip (Banik et al, 2020;Begum et al, 2020;Hanefeld et al, 2015;Hasan et al, 2017). Peattie et al (2005), defined tourist health risk as the probability of suffering from diseases or other health complexities due to the exposure to any traveling experiences.…”
Section: Tourist Knowledgementioning
confidence: 99%
“…Therefore, Floyd and Pennington-Gray ( 2004) also emphasize the importance of the study of the tourist risk perception as there is evidence of association of higher risk with decreased visitation (Deb et al, 2020;Drimili et al, 2020). In the context of the tourism industry, a more comprehensive perspective of understanding tourist perception of risk includes evaluating tourists' health concern both in terms of perception of susceptibility and severity (Banik et al, 2020;Cahyanto et al, 2016). Additionally, Chien et al (2017) expressed that perception of tourists of health risk is one of the critical inputs in tourist's decision-making method Suhartanto et al, 2020).…”
Section: The Mediation Role Of Tourist Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas with high population density, the distance between individuals is shorter and the spread range of individuals is wider. Because of higher contact frequency and more neighbors around them, infectivity and the probability of being infected also increase with the increase of population density [8][9][10]. Thus population density is likely to have an effect on the number of daily cases, and cities or regions or countries with higher population density is likely to hit harder by COVID-19 epidemic.…”
Section: Introductionmentioning
confidence: 99%